Mean Arterial Pressure and Urine Protein Examination as a Prediction of Hypertension in Pregnant Women in the Third Trimester at Prima Husada Sidoarjo Hospital - Masruroh, Nur (Jurusan Kebidanan Poltekkes Kemenkes Sorong, 2025)
hypertension is still a major health problem in the world and in Indonesia. Included in the three main causes of maternal death. Preeclampsia is a complication in pregnancy which is characterized by hypertension and protein in the urine. this study aims to determine the relationship between MAP examination and urine protein examination with hypertension in third-trimester pregnant women at Prima Husada Hospital. This research method is a cross-sectional analytic observation with a sample of 30 pregnant women. MAP is obtained by measuring maternal blood pressure then calculated with the formula to find out the results. Whereas urine protein is obtained by using dipstick. Test analysis with Chi-Square. from 30 respondents found 60% positive on MAP examination and 80% positive contained protein in his urine. The results of the analysis of the relationship between MAP and hypertension obtained p=0,000 (<0.005). On examination of urine protein with hypertension, p=0.272 (> 0.005) was obtained. there is a relationship between MAP examination with hypertension and there is no relationship between urine protein and hypertension. It is expected that pregnant women routinely check pregnancy at least 4 times during pregnancy and midwives conduct early detection of preeclampsia to prevent complications in the mother and fetus